(untitled) (Economic and Political Thought, 2023)
Differentiated integration has been a well-established concept and a part of political programmes in Europe for last 40 years. Author argues that politisation of the project and growing Eurosceptic tendencies transform it from rather innocent tool to enhance integration and wait for some member states into potentially dangerous framework for peripherisation. Building European policy on the rejection of Europeanisation was adopted as a tactic by Hungary in 2010 and Poland in 2015 and the possibility of peripherisation of Vysehrad subregion in the EU became real. War in Ukraine weakened the tensions but structurally the issue is still important – differentiated integration has changed its principal function.